HEALTH LITERACY QUESTIONNAIRE: REPORT ON THE EXPERIENCE OF RESEARCHERS IN PRIMARY CARE - Cavalcanti, Euni de Oliveira; Brito, Anny Kelly da Silva Santos; Góis, Maria Isabel Bezerra; Bezerra, Joana D'arc da Rocha; Ramos, Ana Beatriz Soares; Paranaguá, Thatianny Tanferri de Brito (Cogitare Enfermagem, 2024)
Objective: To analyze themes that emerged from the experience of researchers during the application of the Health Literacy Questionnaire in primary health care. Method: The experience report is based on the researchers' field diary, collecting data from 500 primary healthcare users in the Federal District - of Brazil between May and August 2022. The records were analyzed in the light of Nola Pender's nursing theory. Results: Demands for care emerged as the main category associated with poor quality of care. The perception of a precarious health system was revealed, implying a low level of relevance perceived by users about their cooperation in promoting changes in health services. Final considerations: It was possible to understand the role of the nursing team in involving users in their care and how this directly reflects on health promotion and disease prevention.